The factors leading to work stress and its impact on employee’s performance among support service staff in KPJ Rawang Specialist Hospital / Afiqah Mohamad Zamri - Mohamad Zamri, Afiqah (2017)
The main objective of this research is to study the factors leading to work stress and its impact on employee performance. The factors leading to work stress and its impact on employee performance is vital for any organization to ensure its success and smooth functioning. From the total of support service employees, 107 were selected as respondents for the study. Questionnaire method mainly used to gather the primary data. Secondary data from relevant resources have also effectively utilized in this research to reach valid theoretical findings and conclusions. This research mainly involves 5 chapters, namely Introduction, Literature Review, Research Methodology, Finding and Analysis, Conclusion and Recommendation. SPSS software was used to examine those data which were collected and also to generate the final result. The result shows that, there are significant correlations between independent variable (workload, work life balance and social support) and dependent variable (employee performance). The major findings, limitations for the study, implications of the study and recommendations of this study will be discussed.